Is Virtue Self-sufficient for Happiness?: Augustine on Virtue and Happiness (Journal for the Study of Religion and History (JSRH), 2025)
The paper investigates whether Augustine adheres to the Stoic assertion that “virtue is self-sufficient for happiness,” especially whether Augustine still maintains the self-sufficiency of virtue in this imperfect life. This paper will first present how Augustine adopts the self-sufficiency of virtue in his earlier writings. After that, this paper will show how Augustine criticizes the self-sufficiency of virtue in this life by emphasizing original sin. Lastly, this paper argues that Augustine redefines virtue by introducing the concept of love, through which he redefines the cardinal virtues and theological virtues. Grounded in the idea of love, Augustine contends that properly ordered love can contribute to happiness in this life. In a word, virtue is also self-sufficient in this life, but only when received as love from God.